Balancing Stability and Growth: The Role of Interest Rates and Deposit Insurance in Shaping Inflation and Economic Resilience in ASEAN - Suhardiono Suhardiono; Roy Sembel; Adler Haymans Manurung (Universitas Batanghari Jambi, 2026)
This study examines the effects of interest rates and deposit insurance agency presence on inflation and GDP growth in ASEAN countries from 2019 to 2023. Using a quantitative approach with linear regression analysis, the findings reveal that higher interest rates are associated with lower inflation, highlighting the effectiveness of monetary policy in managing price stability within the region. Additionally, the existence of deposit insurance agencies positively impacts both inflation and GDP growth. While deposit insurance enhances financial stability and fosters economic growth by boosting public confidence, it may also contribute to inflation through increased consumer and investment activity. These findings suggest that ASEAN policymakers should adopt a balanced approach, combining interest rate adjustments for inflation control with carefully managed financial stability measures to support sustainable growth. This study provides valuable insights into the roles of monetary and financial stability policies, underscoring the importance of an integrated policy framework to achieve economic resilience in emerging markets. Future research could explore the interaction between these policies and other structural factors to develop comprehensive strategies for sustaining growth in the ASEAN region.